Clinical Manifestations of Sotos Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The major clinical criteria for the diagnosis of Sotos syndrome were evaluated by geneticists in a retrospective analysis of patients examined at the Children's Hospital, Goudi, Athens, Greece.